Electrical and thermal properties of the interface at diffusion-bonded and soldered 304 stainless steel and copper bimetal - Yilmaz, O; Çelik, H (Elsevier Science Sa, 2003)
The 304 stainless steel and copper were joined by diffusion bonding and soldering with different bonding conditions. The microstructure of the interfaces of diffusion-bonded bimetal was investigated by scanning electron microscopy (SEM) and X-ray diffraction (XRD). Electrical resistivity of the interface of the diffusion-bonded samples (ERIDB) and electrical resistivity of the soldered interface (ERIS) were measured in the temperature range 260-370 K. By the increase of temperature, ERIDB and ERIS gave different results subject to electrical current direction. It was also seen that, ERIDB started to increase at lower temperatures than ERIS. In addition to the change of electrical resistivity by temperature, the relations between current and potential difference (I-V) were assessed as function of temperature. According to these results, it was observed that the current obtained on the interfaces of diffusion-bonded sample is more sensitive to voltage than the current measured on the interface of soldered samples. Moreover, the current measured on the interface of diffusion-bonded sample was higher than the value obtained on the interface of soldered bimetal for each current direction. Thermal conductivities of the interface of diffusion-bonded (TCIDB) and thermal conductivities of the interface of soldered bimetals (TCIS) were detected and compared with each other. It has been detected that, TCIDB and TCIS changed according to a linear function by increasing temperature. TCIS did not change by a considerable amount with electrical current direction. However, the intermetallic phases propagated at diffusion-bonded interface changed thermal conductivity values by an excessive amount with the change in electrical current direction. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: diffusion welding; electrical conductivity; soldering